Clinical Impact of Genomic Information in Pediatric Leukemia - Lalonde, Emilie; Wertheim, Gerald; Li, Marilyn M. (Frontiers in Pediatrics, 2017)
Pediatric leukemia remains a significant contributor to childhood lethality rates. However, recent development of new technologies including next-generation sequencing has increased our understanding of the biological and genetic underpinnings of leukemia, resulting in novel diagnostic and treatment paradigms. The most prevalent pediatric leukemias include B-cell acute lymphoblastic leukemia (B-ALL) and acute myeloid leukemia (AML). These leukemias are highly heterogeneous, both clinically and genetically. There are multiple genetic subgroups defined by the World Health Organization (WHO), each with distinct clinical management. Clinical laboratories have started adopting genomic testing strategies to include high throughput sequencing assays which, together with conventional cytogenetic techniques, enable optimal patient care. This review summarizes genetic and genomic techniques used in clinical laboratories to support management of pediatric leukemia, highlighting technical, biological and clinical advances. We illustrate clinical utilities of comprehensive genomic evaluation of leukemia genomes through clinical case examples, which includes the interrogations of hundreds of genes, and multiple mutation mechanisms using next generation sequencing technologies. Finally, we provide a future perspective on clinical genomics and precision medicine.